2021
DOI: 10.1177/19714009211012353
|View full text |Cite
|
Sign up to set email alerts
|

Positive predictive value and stroke workflow outcomes using automated vessel density (RAPID-CTA) in stroke patients: One year experience

Abstract: Purpose Several new techniques have emerged for detecting anterior circulation large vessel occlusion by quantifying relative vessel density including RAPID-CTA, potentially allowing for faster triage and decreased time to mechanical thrombectomy. We present our one-year experience on positive predictive value of RAPID-CTA for the detection of large vessel occlusion in patients presenting with stroke symptoms and its effect on treatment time and clinical outcomes. Materials and methods Three hundred and ten pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…One limitation of this study is that we did not evaluate the impact of these tools on clinical outcomes. Other studies have previously shown a significant improvement in transfer times of LVO patients ( 10 ), but there are mixed results at comprehensive stroke centers ( 9 , 11 13 ). This study included a relatively small sample size at a single institution which may limit generalizability.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One limitation of this study is that we did not evaluate the impact of these tools on clinical outcomes. Other studies have previously shown a significant improvement in transfer times of LVO patients ( 10 ), but there are mixed results at comprehensive stroke centers ( 9 , 11 13 ). This study included a relatively small sample size at a single institution which may limit generalizability.…”
Section: Discussionmentioning
confidence: 95%
“…There are ways for both tools to improve their detection and increase their PPV. A previous paper demonstrated RAPID's PPV could be improved by incorporating a relative vessel density threshold ( 9 ). No similar paper has demonstrated this for CINA LVO to the authors' knowledge and remains a potential opportunity for study.…”
Section: Discussionmentioning
confidence: 99%
“…Radiology AI classification often focuses on the detection of abnormalities on a single scan, but we often care about the difference between successive scans. AI-based classification has hitherto focused largely on classification that distinguishes on a single scan between normal and abnormal/disease states [5,6,7]. While this is helpful to prioritize scans that need further urgent evaluation in the community and emergency room setting, most patients will have essentially normal scans.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies assessed detection of tissue ischemia (all Brainomix, all retrospective, 2 independent of the company, 32,39 total patients n=367), 32,39,40 with sensitivities of 44% to 83% and specificities of 57% to 93% (Table 2). Six studies assessed detection of large vessel occlusion (LVO; 3 vendors, all retrospective, 1 independent of the vendor, 41 total n=2635) 38,[41][42][43][44][45] with sensitivities of 80% to 96% and specificities of 90% to 98%. Only 1 study each assessed hemorrhage detection 46 and MRI diffusion or perfusion imaging.…”
Section: Accuracy Of Ai In Strokementioning
confidence: 99%